2019
DOI: 10.12659/msm.915463
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of Nasopharyngeal Carcinoma by Beta-Lapachone Occurs by Targeting the Mammalian Target of Rapamycin (mTOR)/PI3K/AKT Pathway, Reactive Oxygen Species (ROS) Production, and Autophagy Induction

Abstract: BackgroundBeta-lapachone has been shown to exhibit potent anti-cancer effects against various cell lines. In the present study, we examined the anti-cancer effects of beta-lapachone, a quinone, against human HNE1 nasopharyngeal carcinoma cells, and also assessed its effects on cellular migration and invasion, autophagy, mTOR/PI3K/AKT signalling pathway, and ROS production.Material/MethodsCCK-8 cell counting assay was used to assess cell viability effects after lapachone treatment. Its effects on the mTOR/PI3K/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Intriguingly, these quinones, along with emodin (Mischitelli et al, 2016b) and NSC-95397 (Mischitelli et al, 2016a), cause redox imbalance in RBCs, which LAP does not (Figure 5). This is in contrast to the oxidative properties of LAP observed in nucleated cells (Bey et al, 2007;Han et al, 2019;Li et al, 2014;Park et al, 2011;Torrente et al, 2020), which may be accounted for by differences in metabolic demands between normal and cancer cells. Notably, we have previously shown that N,N-diethyl-3-methylbenzamide (DEET) and triclosan, two other pro-eryptotic compounds, similarly do not elicit oxidative stress in RBCs .…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Intriguingly, these quinones, along with emodin (Mischitelli et al, 2016b) and NSC-95397 (Mischitelli et al, 2016a), cause redox imbalance in RBCs, which LAP does not (Figure 5). This is in contrast to the oxidative properties of LAP observed in nucleated cells (Bey et al, 2007;Han et al, 2019;Li et al, 2014;Park et al, 2011;Torrente et al, 2020), which may be accounted for by differences in metabolic demands between normal and cancer cells. Notably, we have previously shown that N,N-diethyl-3-methylbenzamide (DEET) and triclosan, two other pro-eryptotic compounds, similarly do not elicit oxidative stress in RBCs .…”
Section: Discussionmentioning
confidence: 65%
“…pyran-5,6-dione, C 15 H 14 O 3 ; LAP), a naphthoquinone that naturally occurs in extracts of Lapacho tree (Lamberti et al, 2013) (Figure 1a), possesses an antitumor activity in vitro and in vivo (Ferraz da Costa et al, 2020). Particularly, LAP has been shown to inhibit colon, prostate, nasopharyngeal, melanoma, hepatocellular, breast, glioma, lung, and pancreatic cancer growth (Bey et al, 2007;Han et al, 2019;Lamberti et al, 2013;Li et al, 2014;Park et al, 2011;Silvers et al, 2017;Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…BLP effectively inhibited the growth of oral squamous cell carcinoma of the HN22 and HSC4 lines by promoting the DNA condensation and formation of apoptotic bodies in the cell nucleus (Jeon et al, 2015). This substance induced autophagy and suppressed the migration and invasion of HNE1 nasopharyngeal carcinoma cells (Han, Shi, & Li, 2019). In addition to the studies regarding human species, the cytotoxic action of this substance has recently been demonstrated in canine osteosarcoma cells (Cruz et al, 2018).…”
Section: Resultsmentioning
confidence: 95%
“…It has been demonstrated that the mTOR/PI3K/Akt signaling pathway is triggered in tumor cells and is considered to be a key therapeutic target for the treatment of various cancer types ( 48 ). Han et al ( 49 ) demonstrated that β-rapazone may block the mTOR/PI3K/Akt signaling pathway, induce autophagy, and ultimately inhibit the migration and invasion of nasopharyngeal carcinoma cells. In addition, angiogenesis may provide nutrition and oxygen to tissues, which are essential for tumor growth and metastasis.…”
Section: Signaling Pathways In Autophagy and Tumorsmentioning
confidence: 99%